2017
DOI: 10.17507/jltr.0803.05
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian EFL Students’ Perceptions on the Implementation of Flipped Classroom Model

Abstract: Abstract-The flipped classroom model has gained popularity in education recently. In this model of learning, the students learn materials (e.g., by watching lectures through video) at home, and then they learn more actively in the school classroom. Although flipped classroom model has been popular, the implementation of flipped classroom in an English as a Foreign Language (EFL) context has not been widely published. This article reports results of research examining students' perceptions on the implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 12 publications
7
59
0
1
Order By: Relevance
“…The research on the flipped classroom in Indonesia is still limited. One of which was conducted by Afrilyasanti et al, (2017) who observed Indonesian EFL students" perceptions on the implementation of the flipped classroom model. They took state senior high school students in Malang as the research participants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research on the flipped classroom in Indonesia is still limited. One of which was conducted by Afrilyasanti et al, (2017) who observed Indonesian EFL students" perceptions on the implementation of the flipped classroom model. They took state senior high school students in Malang as the research participants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The purpose of this questionnaire is to measure student interest. This questionnaire was used by Yujing (2015) and Afrilyasanti, et al (2017) to find out students' perceptions about flipped classroom model.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Afrilyasanti et al (2017) investigated the perceptions of 30 senior high school students who joined an EFL writing class using flipped classroom model. Data were collected by using questionnaires, immediate interview and observations.…”
Section: Students' Perceptions Of Flipped Classroomsmentioning
confidence: 99%
“…Flipped classes have been used in different areas but still it needs more in-depth research. Webb et al (2014) and Afrilyasanti et al (2017) emphasize that although flipped classroom model has been popular, the implementation of flipped classroom in an English as a Foreign Language (EFL) context has not been widely published.…”
Section: Introductionmentioning
confidence: 99%